Isovalues of admissible soil capacity for superficial foundations in the Seven Sector of the district of Alto de la Alianza, Tacna 2017. - Maquera Cruz, Pedro Valerio (2018)
This thesis analyzes the problem of the use of soils for foundations of houses in areas or lands not enabled or possessed by invasions. The objective is to characterize the admissible capacity of the ground for superficial foundations of sector seven of the district of “Alto de la Alianza”, Province and Region of Tacna. 2017. Prospective research, the population is referred to the soils of the area and the sample corresponds to the pits studied. The results of the soils of the explorations carried out indicate that the physical properties are similar, the soil being a non-plastic silty sand. The cohesion has been considered zero for being a sandy loamy soil, and the angle of friction in average of 30 ° in natural state. The value of the admissible load capacity has been calculated for surface foundations at different depths of slab and for different foundation widths. We conclude a characterization of isovalues of the admissible soil capacity that are below 1 kg / cm2 for a depth of 0.80 m and 1.20 m. with a foundation width of 1.0 x 1.0m.